Against the Most Grievous Evils Combated by Religion and the State: Inquisition and Church in Cuba at the beginning of the 19th century - Fernández Mellén, Consolación (2019)
Between 1810 and 1824 the Spanish Antilles witnessed the beginning, maturation and culmination of Independence in the continental American territories, while Spain—beginning with the French invasion of the Iberian Peninsula in 1808—lived through its first two experiences with Liberalism. Neither of these historical developments would have been possible without the subversion of the absolute monarchy—at that time in the person of Fernando VII—, the consequences of which were perceived in the islands. After the restoration of absolutism, emerging voices in Cuba tried to adapt inquisitorial structures to the new reality that, imposed by external events, conditioned the development and effective action of the Inquisition on the islands. This article aims to reconstruct a project to establish a new Inquisition tribunal in Havana, which was presented as an appropriate instrument for the control of ideas, the defense of religion and against heresy.